Data associated with the characterization and presumptive identification of Bacillus and related species isolated from honey samples by using HiCrome Bacillus agar - Alippi, Adriana Mónica (2019)
The dataset described in this paper provides information on the morphological features of 24 different species of the genera Bacillus, Paenibacillus, Brevibacillus, Lysinibacillus, and Rummeliibacilluswhen growing in HiCrome Bacillus agar. The species studied are common contaminants of honey. In support to the recent publication entitled “HiCrome Bacillus agar for presumptive identification of Bacillus and related species isolated from honey samples” (2), a collection of 197 bacterial isolates belonging to 24 different species of aerobic spore-forming bacteria have been screened for their colony appearance and color and any substrate color change of HiCrome Bacillus agar at 24 and 48 h of incubation. Two simple flowcharts utilizing a combination of colony and media characteristics in the chromogenic medium and a set of simple biochemical and morphological tests were developed for quick presumptive identification.